“For there is still a vision:” Metz’s Apocalyptic Eschatology and the Practice of Lament - Reynolds, Susan (Lumen et Vita, 2015)
This paper will explore the place of hope in communal practices of lament through the lens of German political theologian Johann Baptist Metz’s apocalyptic eschatology. The cultivation and articulation of hope is a critical dimension of practices of lament that emerge from communities wounded by violence and injustice. Mourning occasions a radical “no” to innocent suffering and invites a hopeful “yes” to a humanizing vision of the future wherein this evil is subverted. Hope, for Metz, is an expression of faith in the capacity of God to interrupt history on behalf of suffering people. To “suffer unto God” (Leiden an Gott) – to cry out to God, to lament – is a posture of radical faith in the promise of God’s Kingdom. It is a mystical disposition of discipleship that confronts human suffering with open eyes by exculpating neither humanity nor God from responsibility and by refusing the false balm of easy answers. In this way, apocalyptic hope becomes an expression of resistance as it nurtures creative praxis in the midst of ongoing suffering and in solidarity with the victims of history and society. The power of apocalyptic language throughout history, especially among the oppressed, is a testament to its resonance. African American spirituals that emerged out of the experience of enslavement draw heavily on apocalyptic language and imagery. Today, we see apocalyptic motifs arise in Christian reflection and action in response to racial injustice in Ferguson and Staten Island. Yet apocalypticism has also evoked discomfort among contemporary theologians who critique its possible glorification of violence, reliance on dualistic thinking, and the scientific implausibility of its temporal claims. Critics of Metz’s apocalyptic eschatology argue that an emphasis on hope in a God who has promised to interrupt history has the opposite effect of being incoherent or apathy-inducing and in either case paralyzing. While acknowledging the validity of such critiques, I will argue, following Metz, that a re-appropriation of apocalyptic rhetoric in a contemporary understanding of lament adds necessary depth to our understanding of hope in the midst of radical and unjust suffering.